A review of typical water pollution control and cost-benefit analysis in China - Feng, Shicheng; Wang, Weimin; Huang, Renliang; Su, Rongxin (Frontiers in Environmental Science, 2024)
This study summarized and evaluated the cost-benefit analysis methods for typical water environment pollution control measures in China. We conducted a comprehensive comparison of these measures, whose advantages and disadvantages were examined, so the application models and characteristics can be delved into. Through integrating methods and analyzing application cases, we refined a combination of measures with high efficiency and low cost in controlling China's water environment. In our analysis of cost-benefit, we emphasized the importance of implementing scientifically designed control measures and employing rigorous methods to addressing water environment pollution. In order to achieve rapid response and efficient treatment of China's environmental problems, we advocated for establishing a cross regional pollution control mechanism. That is, the collaborative platform and scientific suggestions for all participants in this field should be provided, through interdisciplinary integration, development of domestic models, and expansion of databases.